Previously implanted mitral surgical prosthesis in patients undergoing transcatheter aortic valve implantation: Procedural outcome and morphologic assessment using multidetector computed tomography. - Makoto Tanaka; Ryo Yanagisawa; Fumiaki Yashima; Takahide Arai; Masahiro Jinzaki; Hideyuki Shimizu; Keiichi Fukuda; Yusuke Watanabe; Toru Naganuma; Shinichi Shirai; Motoharu Araki; Norio Tada; et al. (PLoS ONE, 2019)
Transcatheter aortic valve implantation (TAVI) in the presence of a preexisting mitral prosthesis is challenging and its influence on the morphology of mitral prosthesis and the positioning of transcatheter heart valve (THV) is unknown. We assessed the feasibility of TAVI for patients with preexisting mitral prostheses, its influence on mitral prosthesis morphology, and the positional interaction between a newly implanted THV and mitral prosthesis using serial multidetector computed tomography (MDCT). Thirty-one patients with preexisting mitral prosthesis undergoing TAVI were included. MDCT was performed before and after TAVI. Thirty patients successfully underwent TAVI without interference from preexisting mitral prosthesis. Although opening disturbance of the mechanical mitral prosthesis by the THV edge was observed in 1 patient, the patient was managed conservatively. No THV embolization occurred. THV shift during deployment occurred in 9 patients and was predicted by a larger aortic annulus area (odds ratio: 1.24 per 10 mm2, 1.03-1.49, p = 0.02), possibly because of large THVs. The mitral mean pressure gradient was slightly higher after TAVI (3.7 vs. 4.3 mmHg, p = 0.002), whereas the mitral regurgitation grade was similar. MDCT showed that the size of the mitral prosthesis housing was unchanged after TAVI. The median distance between the mitral prosthesis and THV was 2.6 mm. The postprocedural angle between the mitral prosthesis and THV was larger than the preprocedural angle between the mitral prosthesis and the left ventricular outflow tract (64° vs. 61°, p = 0.03). Thus, TAVI is feasible in the case of preexisting mitral prosthesis. Serial MDCT demonstrated favorable THV positioning and unchanged mitral prosthesis morphology after TAVI.